Peningkatan Kinerja Pengrajin Patchwork di Jawa Timur Melalui Pelatihan Intensif dan Kondusifitas Lingkungan Kerja - Peggy Lia Ayu Sukma; Widiya Dewi Anjaningrum (Jurnal Ecogen, 2022)
The research was conducted with the aim of knowing whether or not the influence of incentive training and a conducive work environment on the performance of patchwork craftsmen in East Java was strong. Two hundreed craftsmen have been selected as respondents through accidental sampling technique. Quantitative data collected through online and offline questionnaires were analyzed using PLS-analysis. The results beared out that both the intensive training attended by the craftsmen to improve skills in producing patchwork and knowledge of business management as well as the conduciveness of the work environment had a significant influence on performance. The limitation of this research is that it has not differentiated performance based on the demographics of the craftsmen and has not analyzed the types of training that have the most impact on performance. However, the results of this study contribute to the science of HRM which focuses on creative endeavors such as patchwork that there is a strong relationship between training and the work environment with the performance of craftsmen. Also contributing to patchwork craftsmen so that they continue to take part in trainings that can develop skills and knowledge as well as maintain a conducive work environment.